IMPLEMENTASI PEMBELAJARAN BACA TULIS AL-QUR’AN (BTQ) MELALUI METODE YANBU’A DALAM PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN PESERTA DIDIK - Alfaizun, Muchammad Zulfan; Said, Ali; Surur, Shobihus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2025)
Abstract: Metode Yanbu'a is an approach used to facilitate the process of reading the Qur'an with the aim of achieving good and optimal results. By implementing the Yanbu'a method in teaching Quranic reading and writing (BTQ), it is expected to assist students in learning the Qur'an. This method also aims to provide enlightenment when students feel demotivated, thereby encouraging them to read the Qur'an fluently, correctly, and eloquently. This research was conducted at MTs Hidayatussibyan in Wadaslintang, Wonosobo Regency. The objectives of the study were to describe: 1) the ability of reading and writing the Qur'an at MTs Hidayatussibyan Wadaslintang, 2) the effectiveness of the Yanbu'a method in BTQ teaching at MTs Hidayatussibyan Wadaslintang, and 3) the implementation of the Yanbu'a method in improving the students' Qur'anic reading ability at MTs Hidayatussibyan Wadaslintang. A qualitative descriptive method was employed in this study, with the researcher acting as a passive observer. Both primary and secondary data were collected, using observation, interviews, and documentation. Triangulation of sources and methods was conducted to ensure the validity of the data. The findings of this research are as follows: (1) The ability to read the Qur'an at MTs Hidayatussibyan Wadaslintang varies, indicating that some students find it easier to comprehend the material while others are still struggling with reading the Qur'an. (2) The Yanbu'a method has proven to be effective in BTQ teaching at MTs Hidayatussibyan. By following the appropriate steps of the Yanbu'a method, students are expected to achieve excellent academic performance. Through the implementation of this method, students can read the Qur'an fluently, quickly, correctly, and accurately. Moreover, the Yanbu'a method serves as a motivation for students to become Quran memorizers, inspiring them to memorize and understand the contents of the Qur'an more effectively. (3) The implementation of the Yanbu'a method in BTQ teaching, aimed at improving students' Qur'anic reading ability at MTs Hidayatussibyan Wadaslintang, represents the realization of the school's vision and mission. It strives to educate students to read and write the letters of the Qur'an correctly and proficiently.